Tropical cyclone Lili in the Banda Sea, Indonesia: formation, development, and oceanic interaction - Moksen Siwasiwan; Simon Tubalawony; Yunia Anganetjie Noya (Nekton, 2025)
The Banda Sea serves as Indonesia's central region of water mass circulation and receives water flows from the Pacific Ocean, Indian Ocean, and South China Sea. This unique position facilitates significant interactions between the atmosphere and the ocean. This study aims to assess the dynamic factors supporting tropical cyclone Lili's growth in the Banda Sea. This study uses data from the Climate Data Store (CDS) and Marine Copernicus for May 4-12, 2019. The results show atmospheric dynamics, including the presence of low-pressure zones, high air humidity, and other meteorological factors that support the formation and movement of cyclones. During the study period, oceanographic conditions showed varying wind directions from various sources, hindering the wave formation process. Current patterns were observed moving from Australia through Tanimbar waters towards the Banda, Seram, and Timor Seas. In addition, eddy formation was found in Wetar waters, with downwelling processes occurring in the Banda Sea, while upwelling was detected in eastern Seram waters.